Progress in the Diagnosis and Treatment of COVID-19 in Children: A Review - Wang L (Dove Medical Press, 2021)
Libo Wang,1 Gan Li,1 Chang Yuan,1 Yuele Yang,1 Gongxia Ling,1 Jinyu Zheng,1 Yiyang Zhou,1 Tianlei Zhang,1 Wei Lin,2 Zhenlang Lin2 1Department of Clinical Medicine, Wenzhou Medical University, Wenzhou, 325000, Zhejiang, People’s Republic of China; 2Department of Pediatrics, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, 325000, Zhejiang, People’s Republic of ChinaCorrespondence: Wei Lin; Zhenlang Lin Email linwei1110@163.com; lzlprof2020@163.comAbstract: Coronavirus disease 2019 (COVID-19) has been circulating in many countries around the world, characterized by long incubation period, strong infectivity, strong variability, high population susceptibility and diversified transmission methods. Its causative agent is severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Compared with adult patients, the clinical manifestations of COVID-19 in children are often dominated by mild or asymptomatic infections, but children are also important virus carriers and play an important role in the transmission of the virus. In addition, some children will show excessive inflammatory response and experience serious complications such as multisystem inflammatory syndrome in children (MIS-C). At present, the research on COVID-19 in children is still imperfect. This article will review epidemiological characteristics, the mechanism of action, variant characteristics, clinical manifestations, auxiliary examinations and treatment of children with COVID-19, in order to provide help for the diagnosis, treatment and research of children with COVID-19.Keywords: children, COVID-19, mutation, clinical manifestations, treatment